Expert systems for food safety. (December 2015) - Filter, Matthias; Appel, Bernd; Buschulte, Anja
Highlights: An introduction into the area of expert systems in the domain of food safety is given. Issues hampering practical application of decision support tools are highlighted. A strategy for establishing shared food safety knowledge resources is illustrated. Abstract : The integration of experimental data and expert knowledge in user-friendly software tools has been an ongoing effort in the domain of food safety for more than 20 years. Starting with an overview of currently used definitions for the term 'expert system' (ES) and a brief description of the general system architecture we point to issues that were identified as critical for broad end user acceptance in the years 2013–2015. We briefly discuss the increasing demand for updatability of expert system knowledge bases and limitations originating from certain data-driven algorithms used for model generation. Finally we discuss how a strategy proposed for the establishment of community-driven food safety model repositories can contribute to the development of enhanced decision support systems supporting their broad application in the food sector.